Manufacture of super large tungsten single crystals in the form of rotation bodies - Shapovalov, V.O.; Nikitenko, Yu.O.; Yakusha, V.V.; Gnizdylo, O.M.; Sheiko, I.V. (Вопросы атомной науки и техники, 2020)
The results of researches made at creation of technology of production of super-large single crystals of tungsten in the form of plates and bodies of rotation are presented in E.O. Paton Electric Welding Institute NAS of Ukraine created a unique technology for the production of single crystals of refractory metals in the form of plates 170×160×20 mm, worked out the technology and conducted material studies, which confirmed their quality and gave the basis for further development in this direction. In recent years, the technology of growing super–large single–crystal tungsten in the form of rotating bodies with a diameter of 85 mm has been created.